PEREMPUAN DI PARLEMEN BERJUANG DI TENGAH KERAGUAN - Sundari, Eva Kusuma (Pusat Penelitian Politik, 2011)
Women representation in parliament has been determined 30 by law The 30 gender quota is still considered ineffective in voicing out the problems and needs of women and other marginalized groups One ofthe rootcause ofthe ineffectiveness is the domination ofpatriarchy value and norms over women in which stands that menare better handlingpolitical issues rather than women This domination ofpatriarchal values can be traced back topolitical parties through their commitment in giving or not givingproper and rightpolitical education and equalopportunity to both men and women tofill in the seat ofpolitical arena which is still disadvantage to women